1996
DOI: 10.1007/bf02252931
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between enoxacin, a new antimicrobial, and nimesulide, a new non-steroidal anti-inflammatory agent in mice

Abstract: Convulsions induced by the combination of enoxacin, a new antimicrobial, and nonsteroidal anti-inflammatory drugs including nimesulide, ketoprofen, pranoprofen and loxoprofen sodium, were investigated in mice. The oral administration of nimesulide alone induced clonic convulsions at more than 300 mg/kg. The oral administration of ketoprofen, pranoprofen or loxoprofen sodium induced no convulsion up to 1000 mg/kg, 500 mg/kg and 600 mg/kg, respectively, and that of enoxacin induced no convulsion at more than 500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The interaction potential of nimesulide might also differ from that of other NSAIDs (Perucca 1993). NIMESULIDEÐAN UPDATE Taniguchi et al (1996) demonstrated that the administration of nimesulide alone induced clonic convulsions at a dose greater than 300 mg kg À1 and that enoxicam induced no convulsions even at a dose above 5000 mg kg À1 , in mice. However, a combination of nimesulide (200 mg kg À1 ) and enoxicam (400 mg kg À1 ) induced no convulsions.…”
Section: Drug Interactionsmentioning
confidence: 99%
“…The interaction potential of nimesulide might also differ from that of other NSAIDs (Perucca 1993). NIMESULIDEÐAN UPDATE Taniguchi et al (1996) demonstrated that the administration of nimesulide alone induced clonic convulsions at a dose greater than 300 mg kg À1 and that enoxicam induced no convulsions even at a dose above 5000 mg kg À1 , in mice. However, a combination of nimesulide (200 mg kg À1 ) and enoxicam (400 mg kg À1 ) induced no convulsions.…”
Section: Drug Interactionsmentioning
confidence: 99%
“…The proconvulsive effect of nimesulide in combination with kainate was unexpected in the doses we used (10 mg/ kg), since only extremely high doses (300 mg/kg) have been reported to induce convulsions in mice (Taniguchi et al 1996). Whether nimesulide in therapeutic doses can augment epileptic seizures in humans is unknown, but our observation suggests that nimesulide should be used with caution in patients with convulsive disorders until further experience.…”
Section: Discussionmentioning
confidence: 79%
“…Nimesulide was injected in a constant volume of 0.01 ml/g by the subcutaneous route. The dose of nimesulide was selected based on effective doses published for mice (Gupta et al, 1998;Taniguchi et al, 1996). Delivery times were recorded, and as in Experiment 1, parturition was defined as delivery of the first pup.…”
Section: Methodsmentioning
confidence: 99%